Aras Ören and the (West) German Left. Issue 5 (May 2016) - Gezen, Ela
Abstract: Examining both published and unpublished materials overlooked by existing scholarship, this essay sheds light on the transnational formation of literary and political genres through discussion of Aras Ören. As a poet and activist, Ören was one of the earliest and most significant contributors to the emergence of Turkish‐German literature and was affiliated with political circles and aesthetics of writers such as Bertolt Brecht. While focusing on Aras Ören's key role within Die Rote Nelke (an anti‐fascist union of progressive artists allied with communist class struggle), the essay traces the circulation of Turkish working‐class viewpoints into the world of German literary politics. Two years after joining Die Rote Nelke in 1970, Ören became the chair of its disciplinary collective "Group of Writing Workers, " which actively strove to include workers as well as artists in their cultural–political activities. Ören's transnational orientation shaped his milieu through his poetry and his writings about the politicization of literature, the politics of aesthetics, and the social responsibility of the artist in West Berlin during the early 1970s.